INOVASI PUPUK CAIR BERBASIS LIMBAH ORGANIK: STUDI KASUS WARAKAS, TANJUNG PRIOK, JAKARTA UTARA - Nonon Saribanon; Alvira Noer Effendi; Astri Oktavina; Fauziah Ilmi; Muhammad Firdaus Rafzansani (Jurnal Abdimas Bina Bangsa, 2024)
Challenges in achieving food security are increasingly profound, technological advances, rapid population growth, and changes in consumption patterns that affect the waste management paradigm, creating a context to support the emergence of liquid fertilizer innovation based on organic waste. Warakas is an interesting case study in the effort to achieve sustainable agriculture through organic waste management. The training in Warakas was implemented with a scientific and educational approach aimed at providing better knowledge to the community about the benefits of sustainable organic waste management. The participation of 15 participants reflected positive results, where 85% were active in sorting organic waste, 80% understood the fermentation process, 75% understood the use of additional materials, and 90% of participants showed understanding in utilizing organic waste into organic liquid fertilizer. Community participation contributes to reducing organic waste that can pollute the environment. As a positive step, this initiative creates a sustainable development model in Warakas and surrounding areas and opens up opportunities for improving the community's welfare